Optimization of Wireless Sensor Network Architecture with Security System - Shanshan Wang (Hindawi Limited, 2021)
Wireless sensor network (WSN) is a new type of wireless network. It has many advantages, but there are some problems. These problems make it easier for attackers to analyze network security holes and attack and destroy entire networks. This article designs a security wireless sensor network model. It can resist most known network attacks without significantly reducing the energy power of sensor nodes. First, we cluster the network organization to reduce energy consumption. It also protects the network based on the calculation of trust levels and the establishment of trust relationships between trusted nodes and operates the trust management system based on a centralized method, secondly, on the basis of LEACH agreement, draws lessons from the principle of biological immune system, optimizes the wireless sensor network, and further proposes a new immune system structure suitable for wireless sensor networks. The experimental results show that the wireless sensor network model designed in this paper solves the high-efficiency and energy-saving design task, and the trust management system has satisfactory results in defending against attacks.